Invasive fungal infection after heart transplantation: A 7‐year, single‐center experience. Issue 1 (27th January 2017) - Echenique, Ignacio A.; Angarone, Michael P.; Gordon, Robert A.; Rich, Jonathan; Anderson, Allen S.; McGee, Edwin C.; Abicht, Travis O.; Kang, Joseph; Stosor, Valentina
Abstract: Background: Invasive fungal infections (IFIs) are an infrequent but major complication of heart transplantation (HT). We sought to describe the epidemiology at our institution. Methods: A prospective cohort study of 159 heart transplant recipients was performed from June 2005 to December 2012. IFIs were defined by European Organization for Research and Treatment of Cancer/Mycoses Study Group criteria. Results: By univariate analysis, Hispanic ethnicity was associated with IFI ( P =.01, odds ratio [OR] 7.0, 95% confidence interval [CI] 1.7‐27.9). Subsequently, a multivariate logistic regression was performed adjusting for Hispanic ethnicity, age, and gender. Seventeen IFIs were identified, occurring at a median 110 days post HT (interquartile range: 32‐411 days). Five IFIs (29% of IFIs and 3.1% of all HT) occurred during the HT hospitalization, with 13 IFIs during the first year (incidence 8.2%). Conclusions: The cumulative incidence was 10.7%. IFIs were associated with pre‐ and post‐HT vancomycin‐resistant Enterococcus colonization and/or infection, post‐HT renal replacement therapy, anti‐thymocyte globulin induction, and antibody‐mediated rejection. There were no associations with diabetes mellitus, desensitization, 2R/3R cellular rejection, treatments for rejection, re‐operation, neutropenia, or cytomegalovirus infection. IFIs were associated with death ( P =.02, OR 3.9, 95% CI 1.3‐12.1) and 1‐year mortality ( P <.001, OR 9.0, 95% CI 2.3‐35.7), but not 3‐year mortality. Associations with Hispanic ethnicity must be validated. Optimal strategies for risk reduction and prophylaxis remain undefined.